REDUCING THE GAS PRESSURE DROP IN SUCTION MUFFLERS OF HERMETIC RECIPROCATING COMPRESSORS - Lacerda, J. F.; Gasche, J. L. [UNESP]; Parise, J. F. L. [UNESP]; Arantes, D. M. [UNESP]; INT INST REFRIGERAT (Int Inst Refrigeration, 2011)
The suction muffler of hermetic reciprocating compressors is installed in order to attenuate the noise generated by the gas pulsation of the flow through the suction valve. However, the installation of the suction muffler affects the operation of the compressor owing to gas pressure drop, which causes volumetric and energetic efficiency loss due to the gas specific volume augmentation. Therefore, there is a compromise between sound attenuation and pressure drop increase, which has to be taken into account by compressor designers. In this work, it is presented a numerical solution of the flow through a suction muffler in order to analyze the pressure field and point out the main contributions to the overall pressure drop of the flow. A commercial CFD code was used to perform the numerical simulations and the results were validated by using experimental data. After analyzing the pressure field, the geometry of the muffler was modified intending to decrease the flow pressure drop. The geometric modification produced a 28% reduction on the overall pressure drop, without influencing the sound attenuation.